Salivary and fecal microbiota: potential new biomarkers for early screening of colorectal polyps - Zhang, Limin; Feng, Ziying; Li, Yinghua; Lv, Cuiting; Li, Chunchun; Hu, Yue; Fu, Mingsheng; Song, Liang (Frontiers in Microbiology, 2023)
Objective: We aimed to investigate the differences in salivary and fecal microbiota between patients with colorectal polyps and healthy controls to identify novel noninvasive biomarkers for colorectal polyps. Methods: In this case-control study, we collected salivary and fecal samples from 33 patients with colorectal polyps (CP) and 22 healthy controls (HC) between May 2021 and November 2022. All samples were sequenced using full-length 16S rRNA sequencing and compared with the Nucleotide Sequence Database. Result: Compared to the HC group, the microbial diversity of the CP group increased in saliva and decreased in feces (P < 0.05), whereas the microbiota richness was not significantly different (P > 0.05). The principal coordinate analysis revealed significant differences in β-diversity of salivary and fecal microbiota between the CP and HC groups. Moreover, linear discriminant analysis effect size analysis at the species level identified Porphyromonas gingivalis, Fusobacterium nucleatum, Leptotrichia wadei, Prevotella intermedia, and Megasphaera micronuciformis as the major contributors to the salivary microbiota, and Ruminococcus gnavus, Bacteroides ovatus, Parabacteroides distasonis, Citrobacter freundii, and Clostridium symbiosum to the fecal microbiota of patients with polyps. Salivary and fecal bacterial biomarkers showed Area Under roc Curve of 0.8167 and 0.8051, respectively, which determined the potential of diagnostic markers in distinguishing patients with colorectal polyps from controls, and it increased to 0.8217 when salivary and fecal biomarkers were combined. Conclusion: Compared with healthy controls, the composition and diversity of salivary and fecal microbiota in patients with colorectal polyps were significantly different, with an increased abundance of harmful bacteria and a decreased abundance of beneficial bacteria. Salivary and fecal microbiota-based biomarkers can serve as a promising non-invasive tool for the detection of colorectal polyps.